Capability Versus Imparsiality of Doctors as Medical Disputes Mediators - Muhammad Afiful Jauhani; Ninis Nugraheni; Mohammad Zamroni (SOEPRA, 2020)
Abstract: In medical dispute resolution through mediation, a mediator with the medical qualification will be easier to facilitate the mediation process because of their expertise related to substance, but health workers which have high solidity towards the profession which will make it difficult for them to be impartial.The principal aim of this thesis was to study the doctor’s capability and doctor’s impartiality as a mediator in medical disputes. The issue will be discussed normatively juridically through the statute approach, conceptual approach, and comparative approach with Malaysia, Australia, and Netherland as the comparative country.From this research, it can be concluded that the capability of doctors as mediators of medical disputes lies in the gravity levels of doctors who are commensurate with the context of the dispute. Malaysia, Australia, and the Netherlands have required that mediators need to have an understanding of the substance and have technical knowledge of the problem at hand. A doctor’s impartiality as a mediator in medical disputes will have a tendency of partisanship and conflicts of interest.Keywords: Capability, Impartiality, Doctor, Mediator, Medical Dispute